Occurrence of magnetic reconnection in the heliospheric current sheet - Du, Senbei; Li, Hui; Skoug, Ruth; Steinberg, John; Guo, Fan (Frontiers in Astronomy and Space Sciences, 2025)
We have analyzed the solar wind properties associated with a comparable number of the heliospheric current sheet (HCS) crossing events by Parker Solar Probe (PSP) ranging from 0.07 to 0.3 au and Advanced Composition Explorer (ACE) at 0.99 au. Nearly all PSP events (7 out of 8) show signatures of magnetic reconnection, which are more frequent than the ACE events (5 out of 8) that show reconnection. Because the HCS reconnection events have occurred in a variety of wind speeds and plasma conditions, for each event, we propose to define an approximate aspect ratio (width/length) of HCS as the ratio between the absolute HCS width (derived from observations) and the distance traveled by Alfvén waves over the propagation time of the solar wind. We find that the aspect ratio defined in such a way tends to be smaller than 0.01 for most reconnecting events, and becomes much larger than 0.01 for non-reconnecting events. This analysis also explains the different occurrence rates of reconnection observed by PSP and ACE. Potential consequences of magnetic reconnection at the HCS are discussed.